1988
DOI: 10.1159/000281308
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Therapy of Erectile Dysfunction Using Papaverine and Phentolamine

Abstract: The introduction in 1982 of vasoactive agents for intracavemous injection represents a milestone in the diagnosis and treatment of erectile dysfunction. Two preparations, the single drug papaverine hydrochloride and the combination of phentolamine mesylate and papaverine hydrochloride, hold great promise. In the last few years, the use of vasoactive drugs for evaluation and treatment of erectile dysfunction has become accepted worldwide. This paper explores the diagnostic and therapeutic possibilities and haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…Reported ef®cacy rates with dosages between 30 and 110 mg varied between 27 and 78% and were dependent on dosage and the patient population investigated. 27,32,33 A literature analysis of 19 publications that included 2181 patients overall demonstrated that papaverine produced an average response rate of 61% in in-of®ce testing. 27 The most important side-effects were priapisms in 3 ± 18.5%, which mostly occurred during the titration phase.…”
Section: Vasoactive Intestinal Polypeptidementioning
confidence: 99%
See 1 more Smart Citation
“…Reported ef®cacy rates with dosages between 30 and 110 mg varied between 27 and 78% and were dependent on dosage and the patient population investigated. 27,32,33 A literature analysis of 19 publications that included 2181 patients overall demonstrated that papaverine produced an average response rate of 61% in in-of®ce testing. 27 The most important side-effects were priapisms in 3 ± 18.5%, which mostly occurred during the titration phase.…”
Section: Vasoactive Intestinal Polypeptidementioning
confidence: 99%
“…Fibrotic alterations were seen in 5 ± 30% of patients with an average of 5.7% in 15 retrospective studies (Table 2). 27,32,33 In long-term self-injection trials, papaverine produced liver enzyme elevations in 1.6% of patients, evidence of hepatotoxic potential. 27 In animal studies, papaverine resulted in the highest ®brosis-rate among all the investigated vasoactive drugs.…”
Section: Vasoactive Intestinal Polypeptidementioning
confidence: 99%
“…This problem has been reported in 1.5 -60% of patients treated for 1 y. 8,9 We believe that most of the fibrotic nodules occur in patients who inject themselves very frequently (multiple traumas to the corporeal tissue) and who do not compress the injection site for a sufficient amount of time, with the subsequent development of intracavernous hematomas.…”
Section: Results and Complications Of Vasoactive Intracavernous Injecmentioning
confidence: 81%
“…Prolonged erections are usually encountered during the dose titration phase and have been reported in 2 -15% of patients treated. 8,9 The development of painless fibrotic nodules within the corpora cavernosa may lead to penile curvature. This problem has been reported in 1.5 -60% of patients treated for 1 y.…”
Section: Results and Complications Of Vasoactive Intracavernous Injecmentioning
confidence: 99%
“…Since the discoveries of Virag [1] and Brindley [2] showing that injection of papav erine or phenoxybenzamine into the caver nous bodies may induce erection, intracavernous injections have been used intensively as a diagnostic and therapeutic tool for impotent patients [3,4], The main problem linked to intracavernous injection of papaverine and phenoxybenzamine is a 5-15% risk of pro longed erection which can lead to priapism and/or fibrosis of cavernous bodies [5,6]. In this way, psychogenically or neurogenically impotent patients may become organically impotent [5].…”
Section: Introductionmentioning
confidence: 99%